Data‐driven modeling and control of an X‐ray bimorph adaptive mirror. (24th November 2022) - Gunjala, Gautam; Wojdyla, Antoine; Goldberg, Kenneth A.; Qiao, Zhi; Shi, Xianbo; Assoufid, Lahsen; Waller, Laura
Abstract : A framework for data‐driven characterization of the nonlinear dynamics of a piezo‐bimorph adaptive X‐ray mirror has been developed. Rapid surface shape control and stability to within 2 nm RMS have been demonstrated. Abstract : Adaptive X‐ray mirrors are being adopted on high‐coherent‐flux synchrotron and X‐ray free‐electron laser beamlines where dynamic phase control and aberration compensation are necessary to preserve wavefront quality from source to sample, yet challenging to achieve. Additional difficulties arise from the inability to continuously probe the wavefront in this context, which demands methods of control that require little to no feedback. In this work, a data‐driven approach to the control of adaptive X‐ray optics with piezo‐bimorph actuators is demonstrated. This approach approximates the non‐linear system dynamics with a discrete‐time model using random mirror shapes and interferometric measurements as training data. For mirrors of this type, prior states and voltage inputs affect the shape‐change trajectory, and therefore must be included in the model. Without the need for assumed physical models of the mirror's behavior, the generality of the neural network structure accommodates drift, creep and hysteresis, and enables a control algorithm that achieves shape control and stability below 2 nm RMS. Using a prototype mirror and ex situ metrology, it is shown that the accuracy of our trained model enables open‐loop shape control across a diverse set of states and that the control algorithm achieves shape error magnitudes that fall within diffraction‐limited performance.